2021
DOI: 10.1007/s11469-021-00624-w
|View full text |Cite
|
Sign up to set email alerts
|

Can Cycling Be Addictive? A Qualitative Interview Study Among Amateur Female Cyclists

Abstract: Exercise and healthy eating are proposed as a recommended lifestyle by the World Health Organization with several positive outcomes, including a decrease in pathologies such as diabetes and reduction in mortality rates. However, research suggests that there is the potential for exercise behaviour to become addictive among a small minority of individuals, which detrimentally impacts their lives. The risk of exercise addiction increases for endurance sports, of which cycling is considered one, given the intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Next, it was found that physical exercise dependence correlated positively with difficulties in emotional regulation and with negative affectivity. These results suggest that similar to other behavioral addictions such as pathological gambling (Estévez, Jauregui, et al, 2017;Marchica et al, 2019), there is a relationship between addictive behaviors, emotional regulation difficulties and negative affectivity (Baker et al, 2021;Baker et al, 2004). In the case of physical exercise dependence, the role of emotion regulation is still poorly understood to date (Kun et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Next, it was found that physical exercise dependence correlated positively with difficulties in emotional regulation and with negative affectivity. These results suggest that similar to other behavioral addictions such as pathological gambling (Estévez, Jauregui, et al, 2017;Marchica et al, 2019), there is a relationship between addictive behaviors, emotional regulation difficulties and negative affectivity (Baker et al, 2021;Baker et al, 2004). In the case of physical exercise dependence, the role of emotion regulation is still poorly understood to date (Kun et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…EXD appeared in nine of the 25 studies, though it is not currently included as a specific category in the ICD-11 or DSM-V [ 35 , 37 ]. The addiction-component model, which utilizes criteria for addiction that appears in both behavioral and problematic substance use, has been adopted to diagnose exercise addiction in female cyclists [ 67 ]. Since gambling, a behavioral addiction also diagnosed with the addiction-component model, was added to the ICD-11 in 2022 [ 68 ], it is hoped that exercise may be included as well.…”
Section: Discussionmentioning
confidence: 99%
“…Per the Cyclists' Alliance survey of n = 124 professional female riders, 22% of respondents identified mental health as a reason to consider retiring from the sport ( 18 ). Despite not being classified within the International Classification of Diseases as a mental disorder, exercise addiction can also be prominent in women's cycling ( 56 , 57 ). Exercise addiction may further compromise athlete wellbeing, as it may lead to injury, low energy availability, hypothalamic amenorrhea, or Overtraining Syndrome and associated wide-ranging physical and mental disturbances ( 58 , 59 ).…”
Section: Evidence Of Psychopathology In Women's Cyclingmentioning
confidence: 99%